Double trouble: primary bilateral ovarian neuroendocrine tumours in a patient with prior renal cell carcinoma - Ahmad Affandi, Khairunisa; Hamdan, Asmah Hanim; Abd. Fuaat, Azliana (College of Pathologists, Academy of Medicine Malaysia, 2025)
Introduction: Primary ovarian neuroendocrine tumours (NETs) are rare; bilateral involvement is exceptional. This poses a diagnostic challenge in distinguishing primary from metastatic disease, particularly in patients with a prior malignancy. We report a unique case of primary bilateral ovarian NET in a patient with previous clear cell renal cell carcinoma (ccRCC). Case Presentation: A 45-year-old woman with a history of left nephrectomy for ccRCC in 2018 currently presented with enlarging bilateral ovarian masses on surveillance imaging. Computed tomography showed multiloculated cystic masses without evidence of ccRCC recurrence. She underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy. Results: Gross examination of both ovaries showed solid-cystic, tan-yellow tumours (Right: 10 cm; Left: 12 cm). Microscopically, both tumours showed uniform cells in tubular and trabecular patterns with round nuclei, “salt-and-pepper” chromatin, and eosinophilic cytoplasm. Mitoses were low (1/10 HPF) with no tumour necrosis. Immunohistochemistry showed positivity for neuroendocrine markers (CKAE1/AE3, synaptophysin, and chromogranin A). Ki-67 proliferative index was 5%. Tumour cells were negative for renal, sex cord-stromal, germ cell, gastrointestinal, and hormonal markers; supporting a diagnosis of NET grade 2. Discussion: This case highlights an exceptionally rare presentation of primary bilateral ovarian NETs, with added complexity from a prior malignancy. It underscores the importance of integrating histopathology, immunohistochemistry, and clinical history to distinguish rare primary tumours from metastases. Accurate diagnosis is critical for optimal patient management and prognosis.